2010
DOI: 10.1186/1471-2350-11-85
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9gene polymorphisms in nasal polyposis

Abstract: BackgroundMatrix metalloproteinase (MMP) is involved in the upper airway remodeling process. We hypothesized that genetic variants of the MMP-9 gene are associated with cases of chronic rhinosinusitis with nasal polyposis.MethodsWe conducted a case-control study where 203 cases of chronic rhinosinusitis with nasal polyposis and 730 controls were enrolled. Three tagging single nucleotide polymorphisms (SNPs) and one promoter functional SNP rs3918242 were selected. Hardy-Weinberg equilibrium (HWE) was tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…The presence of the combined rs17577GG and rs3787268 GA + AA genotypes for both ER + and HER-2 -patients might jointly decrease DFS and DDFS. This SNP was also shown to be related to the risk of skin squamous cell carcinoma (Nan et al, 2008), endometriosis (Han et al, 2009), nasal polyposis (Wang et al, 2010), and childhood pollinosis (Inoue et al, 2012). Moreover, the A allele in rs17577 was proven to improve survival of nonsmall-cell lung cancer patients ( Jin et al, 2009) similar to our result.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The presence of the combined rs17577GG and rs3787268 GA + AA genotypes for both ER + and HER-2 -patients might jointly decrease DFS and DDFS. This SNP was also shown to be related to the risk of skin squamous cell carcinoma (Nan et al, 2008), endometriosis (Han et al, 2009), nasal polyposis (Wang et al, 2010), and childhood pollinosis (Inoue et al, 2012). Moreover, the A allele in rs17577 was proven to improve survival of nonsmall-cell lung cancer patients ( Jin et al, 2009) similar to our result.…”
Section: Discussionsupporting
confidence: 88%
“…This missense mutation is located in the hemopexin-like domain and probably functions in substrate binding (Li et al, 1995), and through in silico molecular modeling, it was suggested that this mutation may alter MMP9 activity by interacting with PEX9 and TIMP1 (Rodius et., 2011). It is worth noting that this tagging SNP is in a strong LD with an MMP9 promoter SNP, rs3918242 ( -1562C > T) (Han et al, 2009;Jin et al, 2009;Wang et al, 2010;Inoue et al, 2012), which might alter the MMP9 gene transcriptional activity and influence the enzyme production (Zhang et al, 1999). Taken together, these studies imply that rs17577 is likely to have influence in some subgroups of breast cancer patients through MMP9-related tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 89%
“…The expression of MMP9 mRNA was higher in nasal polyps when compared with inferior turbinate mucosa in patients with chronic rhinosinusitis. 36 Wang et al 37 reported that -1590C/T and R668Q were associated with chronic rhinosinusitis with nasal polyposis. The haplotype corresponding to H3 in our study was also associated with the disease (P¼0.0045).…”
Section: Discussionmentioning
confidence: 99%
“…The amplification was performed in a total volume of 25 l, containing 100 ng of genomic DNA, (1×) Taq polymerase buffer, 3 mM MgCl 2 , 0.6 mM of a dNTP-Mix, 10 pmol of each primer, 1 U of Taq DNA polymerase and water. The primers used for amplification and the T m are listed in Table 2 [21,22]. The volume of the restriction assays was 25 l containing 10 l of the PCR product, buffer, and 5 U of the appropriate restriction enzyme (Fermentas) are summarized in Table 2.…”
Section: Mmp-9 Genotypingmentioning
confidence: 99%